SOCIAL ETHICAL CONTEXT OF SOCIAL RESEARCH - Mesía Maraví, Teodoro Rubén (2014)
The article at hand is intended to examine briefly the delicate ethical question that has to be considered when social researches are carried out, as a result of educational investigations. The ethical question is not always an obvious one, it is frequently ambiguous or something no one is aware of. That’s why it is necessary to have certain formal codes that can define acceptable behaviors. In other words, the existence of specific norms will be responsible, in the context of investigations, especially investigations about human beings, of not hurting the participant, providing a fair and equivalent treatment and, besides, the right to privacy because, often, in social research there is a high level of intrusion in people’s private life.